TEACHING READING NARRATIVE TEXTS THROUGH STORY IMPRESSION STRATEGY TO ISLAMIC JUNIOR HIGH STUDENTS - Suryani Suryani (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2017)
The objectives of this study were to find out whether or not there were a significant difference and a significant improvement on the eighth grade students’ achievement in reading narrative text between those who were taught by using Story Impression strategy and those who were not. In this study, quasi experimental design was used. The sample of the study was taken by using convenience sampling technique consisted of 60 students. This study was conducted for about a month and a half consist of twelve meeting including pre-test and post-test. The instrument used in collecting the data was multiple choices test. The test was administered twice, as the pre-test and post-test for both control and experimental group. The result of the test was analyzed by using independent sample t-test, paired sample t-test and percentage analysis, it was found that there was a significant difference between students’ posttest experimental and control group, since the p-output (0,038) was lower than 0.05 and t-value (2.126) was higher than t-table (1.966). Furthermore, there was a significant improvement both of group, since p-output (0.024), was lower than 0,05 and t-value (2.386) was higher than t-table (2.042).